Photochemical and Thermal 1 Stability of some Dihydroxyacetophenones used as UV-MALDI-MS Matrices - Tarzi, Olga Inés (2013)
2,4-, 2,5-, 2,6- and 3,5-dihydroxyacetophenone (DHA) used as matrices in matrix-assisted ultraviolet laser desorption/ionization mass spectrometry (UV-MALDI-MS) were studied by steady-state and transient absorption spectroscopy, together with DFT calculations at the B3LYP level of theory. All compounds have low fluorescence quantum yields, possibly due to an efficient excited-state intramolecular proton transfer (ESIPT). Laser flash photolysis (LFP) results showed that, only for 2,4-DHA, a phototautomer could be detected at k = 400 nm. Their photochemical stability in solution at different wavelengths and conditions was analyzed by UV–Vis and 1 H nuclear magnetic resonance spectroscopy (1 H-NMR), together with thin layer chromatography and ultraviolet laser desorption/ionization mass spectrometry (UV-LDI-MS). Only 3,5-DHA showed decomposition when irradiated, probably because phototautomerization is not possible. Thermal stability studies of these compounds in solid state were also conducted.